Full Factorial Experimental Design for Development and Validation of a RP-HPLC Method for Estimation of Letrozole in Nanoformulations - Hegde, Aswathi R.; Managuli, Renuka S.; Naha, Anup; Koteshwara, Kunnatur B.; Reddy, Meka S.; Mutalik, Srinivas (Current Pharmaceutical Analysis, 2018)
Background: Letrozole (LTZ) is a potent aromatase inhibitor which blocks estrogen synthesis in post-menopausal women. Suitable analytical methods are required to quantify letrozole in bulk and its nanoformulations. Hence a sensitive and robust reverse-phase high performance liquid chromatographic method (RP-HPLC) was developed for the estimation of LTZ. Methods: The method was developed using Kinetex C18 column (250 mm.6 mm; 5μ) and mobile phase comprising acetonitrile (ACN): acetate buffer (pH 4.5) mixture (50:50% v/v) was used to affect the chromatographic separation at 0.8 mL/min flow rate. The responses were measured at 240 nm. Force degradation studies were done by exposing LTZ to acid- and alkali-induced hydrolysis, oxidation (H2O2), thermal and photolysis. Two-level factorial design was used to validate the method as per ICH Q2 (R1) using Design-Expert® software. The effects of independent variables on flow rate, pH, acetonitrile content and column temperature were recorded as responses. Results: Method was linear over the concentration range of 5-2500 ng/mL with a correlation coefficient (R2) of 1.000. Force degradation studies revealed that LTZ was stable to all stress agents except the basic conditions. The inter-day precision results were reproducible with relative standard deviation (% RSD) of 0.078. The peak area RSD and mean recovery of LTZ was found to be <1.0% and 99-102% in drug solution and <1.0% and 98-106% in nanoformulations respectively. Deliberate changes in independent chromatographic parameters analyzed using analysis of variance (ANOVA) indicated that the model was significant (p<0.0001). Conclusion: The developed analytical method was successfully utilized to quantify LTZ in bulk and its nanoformulations.
Keywords: validation